2020
DOI: 10.3390/ijms21114129
|View full text |Cite
|
Sign up to set email alerts
|

CD38 and Anti-CD38 Monoclonal Antibodies in AL Amyloidosis: Targeting Plasma Cells and beyond

Abstract: Immunoglobulin light chain amyloidosis (AL amyloidosis) is a rare systemic disease characterized by monoclonal light chains (LCs) depositing in tissue as insoluble fibrils, causing irreversible tissue damage. The mechanisms involved in aggregation and deposition of LCs are not fully understood, but CD138/38 plasma cells (PCs) are undoubtedly involved in monoclonal LC production.CD38 is a pleiotropic molecule detectable on the surface of PCs and maintained during the neoplastic transformation in multiple myelom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 66 publications
2
16
0
Order By: Relevance
“…A multicentric retrospective study showed the feasibility and effectiveness of DARA in relapsed/refractory AL (Amyloid light chain) amyloidosis suggesting its use early in the course of disease [ 77 ]. Other supporting data can be found in the literature [ 78 , 79 , 80 ].…”
Section: Clinical Applications Outside MMsupporting
confidence: 74%
“…A multicentric retrospective study showed the feasibility and effectiveness of DARA in relapsed/refractory AL (Amyloid light chain) amyloidosis suggesting its use early in the course of disease [ 77 ]. Other supporting data can be found in the literature [ 78 , 79 , 80 ].…”
Section: Clinical Applications Outside MMsupporting
confidence: 74%
“…Our data correlated with those from a previous case report [ 13 ] and with the currently reported results of phase I/II trials for patients with MM [ 14 , 15 ]. A case report of a patient with relapsed plasma cell leukemia and t(11;14) treated with a combination therapy of venetoclax, daratumumab, and dexamethasone showed a rapid decrease in tumor burden [ 13 ].…”
Section: Discussionsupporting
confidence: 91%
“…Among these patients, 46% were refractory to PI, 71% were refractory to IMiDs, and 42% were double refractory to PI and IMiDs. The ORR of patients with t(11;14) treated by VenDd therapy was 92%, while that for patients treated with venetoclax (Ven) in combination with daratumumab (D), dexamethasone (d), and bortezomib (V) (VenDVd) therapy was 88%; this demonstrated a significant efficacy of the combination treatment [ 14 , 15 ]. Our data are also useful for establishing the optimal dose for each of the drugs.…”
Section: Discussionmentioning
confidence: 99%
“…CD38 is a transmembrane glycoprotein molecule that plays an important role in cell adhesion and is heavily present in clonal PCs [ 98 ]. Daratumumab is a humanized monoclonal antibody against CD38 that can initiate antibody-mediated cellular toxicity along with complement-mediated cytotoxicity [ 99 ].…”
Section: Monoclonal Antibodies Targeting Cd38mentioning
confidence: 99%